STUDY OF THE EFFECT OF LOMUSTIN ON HER2-POSITIVE BREAST CANCER IN FVB/N HER-2 TRANSGENIC MICE - A. N. Stukov; S. F. Vershinina; N. A. Koziavin; T. Yu. Semiglazova; L. V. Filatova; D. Kh. Latipova; A. O. Ivantsov; V. G. Bespalov; A. L. Semenov; O. A. Belyaeva; G. S. Kireeva; V. A. Alexandrov; et al. (Сибирский онкологический журнал)
Because of the high risk of brain metastases from HER2-positive breast cancer, the study of the anticancer activity of drugs used to treat brain tumors, in particular lomustine, is of great importance. In the FVB/N Her-2 transgenic mice bearing HER2-positive breast cancer (BC HER2+), a single oral administration of lomustine at a dose of 50 mg/kg resulted in a significant tumor growth inhibition (up to 96 %, p<0.0001). The tumor growth index (TGI) expressed as a ratio between the areas under the kinetic curves of tumor growth in the study and control groups and amounted to 33 % (p<0.001) indicated the high activity of lomustine. However, the effect of lomustine on intramuscularly transplanted Ehrlich tumor was insignificant (tumor growth inhibition and tumor growth index were <39 % and 68 %, respectively). Lomustine administered orally at a single dose of 50 mg/kg 24 hours after intracranial transplantation of BC HER2+ increased the median survival time up to 30 days in FVB/N mice compared to 21 days in the control group mice (p<0.001). The high therapeutic effect of lomustine in HER2-positive breast cancer mice is likely can be explained by the biological characteristics of this tumor; therefore clinical trials of lomustine for HER2-positive tumors are needed.